Variability for cell-wall and yield components in commercial sugarcane (Saccharum spp.) progeny: contrasts with parental lines and energy cane. Issue 6 (2nd November 2022) - García, José M.; Silva, Mariana P.; Simister, Rachael; McQueen-Mason, Simon J.; Erazzú, Luis E.; Gomez, Leonardo D.; Acevedo, Alberto
ABSTRACT: Sugarcane ( Saccharum spp .) is a genetically complex crop with great potential for the second-generation (2 G) ethanol industry. Despite this, there is scarce knowledge of the variability of bagasse cell-wall components and its association with agronomic traits that could be used in the selection of cultivars with improved bagasse digestibility. In this work, the acid detergent fiber method was used to determine cellulose, hemicellulose, and acid detergent lignin (ADL) in a sugarcane progeny from crossing two commercial cultivars, and in two energy-cane biotypes. Additionally, acetyl bromide-soluble lignin was determined and compared with ADL values. Despite the crossed parents showing similar bagasse composition, transgressive inheritance observed in the progeny for all bagasse cell-wall components underlines the possibility of improving sugarcane for specific bioenergetic uses. Additionally, the low association between cell-wall and yield components found in this work, suggests that indirect selection of cell-wall components for 2 G ethanol industry through agronomic traits would have a limited impact on improving the biomass composition.